2017
DOI: 10.1088/1681-7575/aa5ba1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of impedance mismatch and coaxial cable length on absolute gravimeters

Abstract: The systematic effects of absolute gravimeters have to be investigated to fully utilize their capabilities in metrology and geosciences. In Křen et al (2016 Metrologia 53 27-40) we found that for an FG5 gravimeter, even a few meter long coaxial cable used for transmission of fringe signal causes systematic features in residuals and errors at the level of 1-2 µGal. In this paper, we present experimental results and appropriate models to explain the effects that were found to be caused by impedance mismatches o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Therefore, we use a delay of about 31 ms from the top of the free fall as the beginning of the evaluation interval for the FG5X gravimeter. One reason of this practice is that the electronic dispersion of the fringe signal is large at low frequencies [14], which affects the evaluation of the free fall acceleration.…”
Section: Measurement Setup and Evaluation Principlementioning
confidence: 99%
“…Therefore, we use a delay of about 31 ms from the top of the free fall as the beginning of the evaluation interval for the FG5X gravimeter. One reason of this practice is that the electronic dispersion of the fringe signal is large at low frequencies [14], which affects the evaluation of the free fall acceleration.…”
Section: Measurement Setup and Evaluation Principlementioning
confidence: 99%
“…aviation transport). Also, Křen et al (2017Křen et al ( , 2019 identified, characterised and partially removed biases originating in the signal processing chain of FG5 gravimeters, e.g. due to cable length and fringe signal amplitude.…”
Section: Gravimeter Bias and Si Traceabilitymentioning
confidence: 99%
“…γ A = 300 µGal m −1 ) and a zero gradient (obtaining v * 0 and g * 0 ). Next, one can determine the effective measurement height by (7) and finally solve the following linear equation by least squares…”
Section: Theorymentioning
confidence: 99%
“…However, a noise at low (temporal or spatial) frequencies must be taken into account carefully. As an example, the effects of the self-attraction (SAE) [6], cable dispersion and impedance mismatch [7] are shown in figure 3. These effects are usually subtracted from the measured g-values by additional corrections represented by the constant values for a given effect.…”
Section: Perturbations In the Gravity Residualsmentioning
confidence: 99%
See 1 more Smart Citation